Penetapan Kadar Flavonoid Total dari Fraksi Etil Asetat Daun Sirsak (Annona muricata L.) Dengan Metode Spektrofotometri Uv-Vis - Ananda , Nadia; Pulungan, Ainil Fithri; Nasution , Haris Munandar; Daulay , Anny Sartika (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: The use of plants as traditional medicine is supported by their bioactive compounds, particularly secondary metabolites such as flavonoids. Soursop leaves (Annona muricata L.) are known to be rich in these compounds; however, quantitative data, especially in specific fractions, remain limited. Determining the total flavonoid content is essential for the standardization of herbal raw materials. Objective: This study aimed to identify the classes of chemical compounds present in the ethanol extract and ethyl acetate fraction of soursop leaves and to determine the total flavonoid content of both samples. Methods: Soursop leaf simplicia was extracted using 70% ethanol by the maceration method. The resulting ethanol extract was then fractionated with ethyl acetate. Phytochemical screening was conducted to identify compound classes, while the determination of total flavonoid content was quantitatively analyzed using the UV-Vis spectrophotometry method with quercetin as the standard. Results: Phytochemical screening revealed that both the ethanol extract and the ethyl acetate fraction tested positive for alkaloids, flavonoids, tannins, and steroids/triterpenoids. The total flavonoid content obtained in the ethanol extract was 31.524 ± 0.1524 mg QE/g, while the ethyl acetate fraction showed a significantly higher content of 41.425 ± 0.1363 mg QE/g. Conclusion: Fractionation with ethyl acetate effectively concentrated flavonoid compounds from the crude soursop leaf extract, as indicated by the higher total flavonoid content in the ethyl acetate fraction. These findings support the potential of the ethyl acetate fraction of soursop leaves as a source of flavonoids for the development of standardized herbal medicines.